Plasmodium falciparum Malaria Clinical and Parasitological Outcomes after In-vivo Artemether- Lumefantrine (AL) Treatment at Bushenyi District Uganda - Nyabayo Maniga, Josephat; Aliero, Adamu Almustapha; Ntulume, Ibrahim; Okech, Matilda Angela; Claire Mack, Mugasa (International Journal of Tropical Disease & Health, 2018)
The aim of this study was to determine the Plasmodium falciparum malaria clinical and parasitological outcomes after in-vivo Artemether-Lumefantrine (AL) treatment at Bushenyi District Uganda. Study Design: This was a one-arm prospective longitudinal health point survey. Place and Duration: This study was carried out in Bushenyi District Uganda as from May 2017 to August 2017 for a period of four months at the selected four health centers. Methodology: A cohort of 283 human participants who had been confirmed of Plasmodium falciparum malaria was followed for a period of 28 days after treatment with Artemether-Lumefatrine (AL) drug. The follow up was done at fixed check up visits i.e. day 0, 1, 2, 3, 7, 14, 28. Parasitological and clinical evaluations were done at each subsequent follow up days. Consequently they were requested to fill a questionnaire which had aspects of malaria infection. Results: Out of the 283 participants recruited to this study 194 (68.6%) participants completed the follow up schedules while 89 (31.4%) were withdrawn from the study. There was adequate clinical and parasitological response (ACPR) among 53(27.3%) participants. There was late parasitological failure (LPF) among 43 (22.2%) participants. There was late clinical failure (LCF) among 23(11.9%) participants and there was early treatment failure (ETF) among 75 (38.7%) participants Conclusion: There was suspected Artemether- Lumefantrine (AL) poor response to Plasmodium falciparum malaria in the study area after 8 years of introduction to Uganda as a drug of choice for treatment of uncomplicated malaria. Those aged 5 years and below were 2.28 times more likely to present LCF as a clinical treatment outcome compared to other age groups when other factors were held constant. Molecular confirmation of the suspected resistance needs to be conducted in the collected Plasmodium falciparum isolates.
Keywords: Plasmodium falciparum; Cohort; Drug resistance; Artemether- Lumefantrine (AL); Uganda